On smelting cassiterite in geological and archaeological samples: preparation and implications for provenance studies on metal artefacts with tin isotopes - Berger, Daniel; Brügmann, Gerhard; Pernicka, Ernst (Archaeological and anthropological sciences, 2019)
Tin isotope ratios may be a useful tool for tracing back the tin in archaeological metal artefacts (tin metal, bronze) to the geological source and could provide information on ancient smelting processes. This study presents the results of laboratory experiments, which reduced (smelted) synthetic stannic oxide, natural cassiterite and corroded archaeological tin and bronze objects. The overall aim of the study is to find a reliable method for the decomposition of tin ores and corrosion products in order to determine their tin isotopic composition, and to explore possible effects on the tin isotope ratios during pyrometallurgy. We focused on five methods of reduction at high temperatures (900-1100 °C): reduction with CO (plain smelting), reduction with KCN/CO (cyanide reduction), reduction with Na2CO3/CO, reduction with Cu/CO (‘cementation technique’) and reduction with CuO/CO (‘co-smelting’). The smelting products are analysed by means of optical and scanning electron microscopy as well as X-ray diffraction, while their isotope composition is determined with a high-resolution multi-collector mass spectrometer with inductively coupled plasma ionisation. The results show that all five methods decompose synthetic stannic oxide, cassiterite and corrosion products. Ultimately, reduction with KCN is the best solution for analysing tin ores and tin corrosion because the chemical processing is straightforward and it provides the most reproducible results. Reduction with Na2CO3 and copper is an alternative, especially for bronze corrosion, but it requires laborious chemical purification of the sample solutions. In contrast, evaporation of tin and incomplete alloying during plain smelting and co-smelting can cause considerable fractionation among smelting products (Δ124Sn = 0.10 ‰ (0.03 ‰ u−1)). A less precise and even inaccurate determination of the tin isotopic compositions of the tin ores would be the consequence. However, the results of this study help to evaluate the possible influence of the pyrometallurgical processes on the tin isotope composition of tin and bronze artefacts.